PERTUMBUHAN MISELIUM DAN PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA PEMBERIAN BEBERAPA ZPT DAN DOSIS KAPUR PERTANIAN - Lalang Loka Subekti; Istiqomah Istiqomah; Mariyatul Qibtiyah; Mutiara Kusumaningtyas Pitaloka (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Oyster mushrooms are one of the types of consumption mushrooms that are in great demand by the public. The demand for mushrooms continues to increase from year to year both from within and outside the country. Currently, oyster mushroom production needs to be increased due to increasing market demand. One way to increase the production of white oyster mushrooms is by giving growth regulators (ZPT) and agricultural lime with the right application time and concentration. This study aims to determine the effect of giving some ZPT and agricultural lime to increase mycelium growth and production of white oyster mushrooms. The research method used was a complete factorial randomized design, consisting of two factors, each factor consisting of 4 levels, and 3 levels. The type of ZPT is the first factor consisting of No ZPT, ZPT Atonik, ZPT Rootmost, and ZPT Dekamon. While the dose of agricultural lime is the second factor consisting of 1% lime (10gr/baglog), 2% lime (20gr/baglog), and 3% lime (30gr/baglog). Parameters observed included pinhead formation time, number of fruits per sample, fruit hood diameter and fruit weight per sample. The observation results were calculated by analyzing variance (F test) at 5% level. If there was a significant difference between treatments, BNT test was conducted at 5% level. The addition of ZPT Atonik and 1% Lime gave the best results from other treatments.